Tambú Curaçao's African-Caribbean ritual and the politics of memory - Jong, Nanette de 1960- (Indiana Univ. Press, 2012)
As contemporary Tambú music and dance evolved on the Caribbean island of Curaçao, it intertwined sacred and secular, private and public cultural practices, and many traditions from Africa and the New World. As she explores the formal contours of Tambú, Nanette de Jong discovers its variegated history and uncovers its multiple and even contradictory origins. De Jong recounts the personal stories and experiences of Afro-Curaçaoans as they perform Tambu–some who complain of its violence and low-class attraction and others who champion Tambú as a powerful tool of collective memory as well as a way to imagine the future.
Keywords: Gesellschaft; Musik; Tambú (Music) -- Curaçao -- History and criticism; Blacks -- Curaçao -- Music -- History and cricism; Music -- Social aspects -- Curaçao; Blacks -- Curaçao -- Rites and ceremonies; Geschichte; Musikethnologie; Schwarze; Curaçao